Pengembangan Strategi Pemasaran pada Destinasi Wisata Air Terjun Wai Boto di Desa Lapasi-Pasi - Andry Stepahnie Titing; Muhamad Stiadi; Hanif Kurniadi; Suwarto Sunandar; Hendrik Hendrik (LPMP Imperium, 2023)
The targets of this activity are Wai Boto waterfall tourism managers and residents of Lapasi-pasi village, Lambai sub-district, North Kolaka Regency. The aim of this service activity is to provide knowledge about marketing and develop marketing strategies for Wai Boto waterfall tourism. The results of this community service activity are increasing knowledge about marketing and providing alternative new marketing strategies for Wai Boto waterfall tourism, namely: adding supporting facilities or facilities, optimizing social media as a marketing medium, training tourism managers. This strategy can be implemented by managers gradually or directly in order to increase the number of visitors. In this activity, the participants participated in the activity well until the event was finished. The managers and residents want activities like this to be held regularly so that the community has new insights for development, especially for tourism management and village progress.